Superior antibacterial activity of ZnO-CuO nanocomposite synthesized by a chemical Co-precipitation approach. (September 2019) - Jan, Tariq; Azmat, Sohail; Mansoor, Qaisar; Waqas, H.M.; Adil, M.; Ilyas, S.Z.; Ahmad, Ishaq; Ismail, Muhammad
Abstract: Synthesis of highly efficient antibacterial agents has become highly important due to emergence of antibiotic resistance. Herein, Pristine ZnO and ZnO-CuO nanocomposite has been synthesized by simple chemical co-precipitation method and characterized by X-ray diffraction (XRD), microscopic and spectroscopic techniques. The prepared ZnO-CuO nanocomposite is composed of two dimensional nanosheets consisting of hexagonal ZnO and monoclinic CuO crystal phases present in coexistence. Moreover, a minute presence of Cu5 Zn8 cubic phase has been evident in the XRD pattern of ZnO-CuO nanocomposite. Fourier Transform Infrared Spectroscopy (FTIR) spectrum of the prepared nanocomposite has revealed the presence of vibrational modes related to both Zn-O and Cu-O. Photoluminescence (PL) investigations depicted the formation of huge amounts of surface defects in ZnO-CuO nanocomposite as compared to pristine ZnO nanostructures. The prepared ZnO-CuO nanocomposite has efficiently killed Methicillin resistant Staphylococus aureus (s. aureus) bacterium by producing 24 mm of zone of inhibition (ZOI) comparing to 8 mm ZOI produced by pristine ZnO. The superior antibacterial activity of ZnO-CuO nanocomposite has been attributed to oxidative stress generated by electron transfer pathway and reactive oxygen species (ROS) generation. Highlights: ZnO-CuO nanocomposite was chemically synthesized. The nanocomposite was characterized by XRD, TEM, FTIR and PL spectroscopy. XRD results confirmed the formation of nanocomposite. The prepared nanocomposite was found to have huge amounts of surface defects. ZnO-CuO nanocomposite exhibited superior antibacterial activity.